THE EFFECTIVENESS OF FIVE-FINGER HYPNOSIS THERAPY IN REDUCING ANXIETY IN INTRA UTERINE DEVICE TYPE ACCEPTORS - Asmara, Dewi Windy; Primindari, Risya Secha; Amalia, Amirul; Sulistiyowati, Sulistiyowati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
IUD insertion is associated with high levels of nervousness in most people,and anxiety and fear can cause discomfort during IUD insertion. Relaxationtechniques are non-pharmacological techniques used to reduce anxiety andpain by tensing the muscles. Not many have applied the five-finger hypnosisrelaxation technique to reduce pain in both hospitals and health institutions asa learning medium. The purpose of this study was to determine the effect offive-finger hypnosis therapy on the anxiety of prospective IUD acceptors. Thisstudy's research design is pre-experimental research with a research approachusing one group pre-test and post-test. The sample in this study is 30 new IUDacceptors at the Muhammadiyah Hospital in Gresik, which is the criteria. TheWilcoxon statistical test results showed a p-value of 0.000. These resultsindicate a significant difference in anxiety levels before and after theintervention. The five-finger hypnosis intervention reduces the level of anxietyin new IUD acceptors.